Integration of texture and disparity cues to surface slant in dorsal visual cortex - Murphy, Aidan P. (American Physiological Society, 2013)
Reliable estimation of three-dimensional (3D) surface orientation is critical for recognizing and interacting with complex 3D objects in our environment. Human observers maximize the reliability of their estimates of surface slant by integrating multiple depth cues. Texture and binocular disparity are two such cues, but they are qualitatively very different. Existing evidence suggests that representations of surface tilt from each of these cues coincide at the single-neuron level in higher cortical areas. However, the cortical circuits responsible for 1) integration of such qualitatively distinct cues and 2) encoding the slant component of surface orientation have not been assessed. We tested for cortical responses related to slanted plane stimuli that were defined independently by texture, disparity, and combinations of these two cues. We analyzed the discriminability of functional MRI responses to two slant angles using multivariate pattern classification. Responses in visual area V3B/KO to stimuli containing congruent cues were more discriminable than those elicited by single cues, in line with predictions based on the fusion of slant estimates from component cues. This improvement was specific to congruent combinations of cues: incongruent cues yielded lower decoding accuracies, which suggests the robust use of individual cues in cases of large cue conflicts. These data suggest that area V3B/KO is intricately involved in the integration of qualitatively dissimilar depth cues.